2010
DOI: 10.1073/pnas.1001539107
|View full text |Cite
|
Sign up to set email alerts
|

Alarm pheromone habituation in Myzus persicae has fitness consequences and causes extensive gene expression changes

Abstract: In most aphid species, facultative parthenogenetic reproduction allows rapid growth and formation of large single-genotype colonies. Upon predator attack, individual aphids emit an alarm pheromone to warn the colony of this danger. (E)-β-farnesene (EBF) is the predominant constituent of the alarm pheromone in Myzus persicae (green peach aphid) and many other aphid species. Continuous exposure to alarm pheromone in aphid colonies raised on transgenic Arabidopsis thaliana plants that produce EBF leads to habitua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 45 publications
(55 reference statements)
1
37
0
Order By: Relevance
“…Compared with the maize terpene synthase 1, which could produce three sesquiterpenes: (E)-β-farnesene (26%), (E)-β-nerolidol (29%), and (E, E)-farnesol (45%) (Schnee et al 2002), the above four isolated EβF synthases produced only one major sesquiterpene, EβF, indicating these genes were good candidates for manipulating crop plants for aphid control. Indeed, overexpression of a peppermint EβF synthase gene in Arabidopsis thaliana not only repelled aphids but also attracted aphid parasitoids (Beale et al 2006) and the EβF-emitting transgenic plants may have practical applications in agriculture as a result of increased predation on habituated aphids (De Vos et al 2010), demonstrating that genetically engineering of plants to consecutively emit EβF for aphid control was feasible. Although the EβF synthase gene had been isolated from sweet wormwood and in vitro analysis indeed proved that it could convert FPP to the only product of acyclic sesquiterpene EβF (Picaud et al 2005), the function of this gene in other plants remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the maize terpene synthase 1, which could produce three sesquiterpenes: (E)-β-farnesene (26%), (E)-β-nerolidol (29%), and (E, E)-farnesol (45%) (Schnee et al 2002), the above four isolated EβF synthases produced only one major sesquiterpene, EβF, indicating these genes were good candidates for manipulating crop plants for aphid control. Indeed, overexpression of a peppermint EβF synthase gene in Arabidopsis thaliana not only repelled aphids but also attracted aphid parasitoids (Beale et al 2006) and the EβF-emitting transgenic plants may have practical applications in agriculture as a result of increased predation on habituated aphids (De Vos et al 2010), demonstrating that genetically engineering of plants to consecutively emit EβF for aphid control was feasible. Although the EβF synthase gene had been isolated from sweet wormwood and in vitro analysis indeed proved that it could convert FPP to the only product of acyclic sesquiterpene EβF (Picaud et al 2005), the function of this gene in other plants remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Aphid populations are regulated by natural enemies such as ladybird beetles and parasitoid wasps. Despite the effectiveness of biological control, behavioral responses to the threat of predation may allow aphids to persist as pests (De Vos et al 2010). For many pest species of aphids, avoidance of predators involves the release of an alarm pheromone comprising (E)‐β‐Farnesene (EβF), a volatile sesquiterpene, released from the cornicles (aka siphunculi) on the aphids’ abdomen when attacked by its natural enemies (Bower et al 1972; Pickett and Griffiths 1980; Dixon 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the majority of insects, aphids can reproduce clonally and an aphid's embryonic development begins before its mother's birth (Goggin 2007). These traits allow for rapid population growth of aphids in the field due to their parthenogenetic lifestyle, short generation times, and the fact that nymphs of certain aphid species can reach maturity in as little as 5 d (Dixon 1988; Goggin 2007; De Vos et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, we are a long way from fully understanding the impact of risk on prey physiology. For example, de Vos et al (2010) found that aphids exposed to their alarm pheromone up-or down-regulated almost 15 % of the 10,000 genes measured, yet we know little related to the control these genes exert. The field of ecophysiological effects of predation risk is in its infancy and we must move beyond simple stress hormone analysis and delve into other physiological responses and understand their interactive effects to fully appreciate how predation risk shapes system-wide changes in prey.…”
Section: Features Of the Special Issuementioning
confidence: 99%